Early functional changes and plasma GFAP in Swedish families with Autosomal Dominant Alzheimer’s disease mutations - Luckett, Emma S.; Zapater-Fajari, Mariola; Almkvist, Ove; Johansson, Charlotte; Chiotis, Konstantinos; Bucci, Marco; Wall, Anders; Ashton, Nicholas J.; Blennow, Kaj; Zetterberg, Henrik; Rodriguez-Vieitez, Elena; Graff, Caroline; et al. (Springer Science and Business Media LLC, 2026)
We aimed to understand longitudinal associations between Alzheimer’s disease (AD) biomarkers in Autosomal Dominant AD (ADAD) across estimated years to symptom onset (EYO). Forty-five individuals (19 mutation carriers [EYO = −7.9 ± 11.7 years, APP N = 11; PSEN1 N = 8]) from Swedish ADAD families participated. All received baseline 18F-Flurodeoxyglucose (FDG) PET and cognitive testing, and a subset (N = 26) plasma glial fibrillary acidic protein (GFAP) measurement. Follow-up data collection (including 106 FDG scans) was performed over 7.4 ± 6.4 years (visits ranged from 1–5, EYO = −25.8 to +10.3 years in mutation carriers). Mixed effects models were applied to determine longitudinal associations. APP and PSEN1 mutation carriers showed different FDG uptake profiles from EYO = −20 to −10 years, with a hypermetabolism before hypometabolism in PSEN1 mutation carriers. Early increases in plasma GFAP were primarily related to subcortical FDG decreases and cognitive changes in APP mutation carriers compared to non-carriers. We provide evidence for gene-dependent biomarker trajectories in ADAD.